Synthesis, Characterization and Evaluation of Some Pyranopyrazoles and Pyranopyrimidines Derivatives as Antioxidants for Lubricating Oils - Ahmad, Mohammed; Mohammed, Abdul Halim; Ali, Yousif; Al-Messri, Zainab (Iraqi Journal of Science, 2023)
6-Amino-4-(4-hydroxyphenyl)-5-cyano-3-methyl-1-phenyl-1, 4-dihydropyrano [2,3-c] pyrazole (compound 2) was prepared by condensation of 2-(4-hydroxylbenzylidine) malononitrile (compound 1) [which was prepared by Knoevenagel condensation of malononitrile with 4-hydroxy benzaldehyde ] with 3-methyl-1-phenyl-2-pyrazolin-5-one. Reactions of compound 2 with different reagents formic acid, formamide, and ammonium thiocyanate under microwave irradiation leads to the synthesis of 4-(4-hydroxyphenyl)- 3-methyl-1-phenyl-4,6-dihydro- pyrazolo [3', 4':5,6] pyrano [2,3-d] pyrimidine-5-one (compound 3), 4-(4-hydroxyphenyl)- 3-methyl-1-phenyl-4, 6-dihydro- pyrazolo [3', 4':5,6]pyrano[2,3-d]pyrimidine-5-imine (compound 4) and N-[4-(4-hydroxyphenyl)- 3-methyl-1-phenyl-7-thioxo-7,8- dihydropyrazolo [3', 4':5,6] pyrano [2,3-d] pyrimidine-5-yl] thiourea (compound 5) respectively. Moreover a series of Schiff bases 6(a-f) were prepared by reaction of compound 2 with different aromatic aldehydes.The prepared compounds were characterized by FTIR, and most 1HNMR,13CNMR and evaluated as antioxidant additives by blending 1% of each compound with base lubricating oil 60 stock supplied by Midland Refineries Company, Baghdad, Iraq. The formulated blend of compound 6a showed better oxidation stability compared with the base oil (blank), while the oil blend of compound 5 gave higher oxidation stability than the blend with standard antioxidant supplied by Midland Refineries Company.